Possible factors associated with mental health among restaurant employees in Malaysia - Ghazali, Hazrina; Adanan, Nurul Hiza; Abu Bakar, Ainul Zakiah; Ridham Othman, Mohd Amar; Ishak, Maisarah (Human Resources Management Academic Research Society (HRMARS), 2024)
Mental health issues affect every workplace, and they have a significant psychological, social, and economic impact. The former Chairman of National Institute Occupational Safety and Health (NIOSH) Malaysia, Tan Sri Lee Lam Thye highlighted that ignoring mental health factors in the workplace is not only detrimental to the individual employee but also directly affects the productivity and output of any organization. In Malaysia, there has been a three-fold increase in mental health problems among the population, and the cost of mental health illness is projected to reach RM24.7 trillion in the year 2030. There are many factors that contribute to mental health among employees, and it became worse since the COVID-19 pandemic struck the world. This study aims to identify possible factors that affect restaurants employees' mental health, analyses the most influential factors, and lastly to determine the relationship between the influencing factors and mental health. This study tested three independent variables that are working environment, workload and salary. A total of 201 valid and usable questionnaires were collected among restaurant employees in Malaysia. The data was collected using an online survey and analysis was performed using Statistical Package for Social Sciences (SPSS) version 26. The results of workload (mean=3.38), working environment (mean=3.70) and salary (mean=3.22) indicated a score leaning towards agreement. However, the three variables were weakly correlated. A multiple regression also was run to predict the restaurants employee’s mental health with the three independent variables. From the finding, only 8.6% of variance in restaurant industry employees was found to be explained by workload, working environment and salary (R² = 0.086). Although these three variables have little effect on restaurants employees' mental health, these findings may alert the restaurants’ operator on the importance of these variables in order to minimize potential factors that can contribute to mental health at workplace.